(untitled) (Journal of Pakistan Orthopaedic Association, 2023)
Background: Hip fractures, constituting 20% of orthopedic trauma workload, often involve displaced Neck of femur (NOF) fractures. Elderly patients typically undergo Bipolar Hemiarthroplasty (BHA) using Hardinge’s or Moore’s approach. As debate on the preferred approach still persists in literature , this study aims to compare dislocation rates in BHA via Hardinge’s vs. Moore’s approach for displaced (Garden type III & IV) femur fractures. Objective: This study aims to compare the rate of dislocation after Bipolar Hemiarthroplasty (BHA) through Hardinge’s (Direct lateral) versus Moore’s (Posterior) approach. Methodology: It was randomized Control Trial with 60 patients (30 per group) in the Orthopedics Department, comparing Hardinge’s and Moore’s approaches for Bipolar Hemiarthroplasty. Follow-up data was analyzed using SPSS. Patient characteristics were expressed in frequencies, and quantitative data presented as mean ± S.D. A p-value ? 0.05 indicated significance. Limitations included a small sample size and single-center study. Results: This study compares Hardinge Bipolar Hemiarthroplasty (HBH) and Moore Bipolar Hemiarthroplasty (MBH) outcomes in terms of patient demographics and dislocation rates. Demography , medication usage, and osteoporosis prevalence vary between groups. Dislocation rates at different time points show significant differences, notably at 6 months. Independent Sample t-test reveals a <0.05 p-value, indicating a significant association between MBH and dislocation at 6 month. Conclusion: There is a definitive difference in the rate of dislocation after bipolar hemiarthroplasty (BHA) through Hardinge’s versus Moore’s approach in displaced (Garden type III & IV) neck of femur fractures.